Content validity and measurement properties of the Lower Extremity Functional Scale in patients with fractures of the lower extremities: a systematic review - Julia Ratter; Sylvia Pellekooren; Suzanne Wiertsema; Johanna M. van Dongen; Edwin Geleijn; Vincent de Groot; Frank W. Bloemers; Elise Jansma; Raymond W. J. G. Ostelo (SpringerOpen, 2022)
Abstract Background Fractures of lower extremities are common trauma-related injuries, and have major impact on patients' functional status. A frequently used Patient-Reported Outcome Measure (PROM) to evaluate patients' functional status with lower extremity fractures is the Lower Extremity Functional Scale (LEFS). However, there is no systematic review regarding content validity and other measurement properties of the LEFS in patients with lower extremity fractures. Methods A search was performed in PubMed, Embase, Scopus, and Cochrane Library from inception until November 2020. Studies on development of the LEFS and/or the evaluation of one or more measurement properties of the LEFS in patients with lower extremity fractures were included, and independently assessed by two reviewers using COSMIN guidelines. Results Seven studies were included. Content validity of the LEFS was rated 'inconsistent', supported by very low quality of evidence. Structural validity was rated 'insufficient' supported by doubtful methodological quality. Internal consistency, measurement error, and responsiveness were rated 'indeterminate' supported by inadequate to adequate methodological quality. The methodological quality of the construct validity (hypotheses testing) assessment was rated as 'inadequate'. Conclusion The LEFS has several shortcomings, the lack of sufficient content validity being the most important one as content validity is considered the most crucial measurement property of a PROM according to the COSMIN guidelines. In interpreting the outcomes, one should therefore be aware that not all relevant aspects of physical functioning may be accounted for in the LEFS. Further validation in a well-designed content validity study is needed, including a clearly defined construct and patient involvement during the assessment of different aspects of content validity. Plain English summary Bone fractures of the lower extremities are a common injury. During rehabilitation it is essential to evaluate how patients experience their physical functioning, in order to monitor the progress and to optimize treatment. To measure physical functioning often questionnaires (also known as Patient Reported Outcome Measures) are used, such as the Lower Extremity Functional Scale (LEFS). However, it is not clear if the LEFS actually measures physical function, and if its other measurement properties are sufficient for using this questionnaire among patients with fractures in the lower extremities. Therefore, we systematically searched and assessed scientific papers on the development of the LEFS (i.e., its ability to measure physical functioning), and papers on the performance of the LEFS with regard to several measurement properties to identify possible factors that may cause measurement errors. Hereby we have assessed the quality of the studies included. Our main finding was that the LEFS may not measure all aspects of physical function. Given the low quality of the papers included in our study, these findings come with considerable uncertainty. As the LEFS was developed more than 20 years ago, it may not represent physical functioning as we currently conceptualize this. Therefore, we recommend to perform a study in which the content of the LEFS will be evaluated by experts in the field as well as patients, and modify the questionnaire as needed.